Representation of Multiculturalism and Critical Thinking Aspects in EYL Textbook Used in a Bilingual Classroom in Indonesia - Jasmine Fadhillah; Siti Muniroh; Niamika El Khoiri (South Sulawesi Education Development (SSED), 2025)
Multiculturalism and critical thinking are both crucial aspects that need to be incorporated to shape students as global citizens. Thus, this research aims to find the multiculturalism and critical thinking aspects in an EYL Textbook entitled